2010
DOI: 10.1590/s0004-282x2010000300010
|View full text |Cite
|
Sign up to set email alerts
|

Do children with Glasgow 13/14 could be identified as mild traumatic brain injury?

Abstract: Objective: To identify in mild head injured children the major differences between those with a Glasgow Coma Scale (GCS) 15 and GCS 13/14. Method: Cross-sectional study accomplished through information derived from medical records of mild head injured children presented in the emergency room of a Pediatric Trauma Centre level I, between May 2007 and May 2008. results: 1888 patients were included. The mean age was 7.6±5.4 years; 93.7% had GCS 15; among children with GCS 13/14, 46.2% (p<0.001) suffered multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Melo et al . [ 19 ] also indicated that of patients with mild brain injury, neurosurgery was performed in 6.7% and 9.2% had neurological disabilities. In fact, mild brain injury based on GCS score may be associated with significant abnormalities in CT scan, require of neurosurgical procedure and Intensive Care Unit admission.…”
Section: Discussionmentioning
confidence: 99%
“…Melo et al . [ 19 ] also indicated that of patients with mild brain injury, neurosurgery was performed in 6.7% and 9.2% had neurological disabilities. In fact, mild brain injury based on GCS score may be associated with significant abnormalities in CT scan, require of neurosurgical procedure and Intensive Care Unit admission.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas measures of injury severity such as the Glasgow Coma Scale (GCS) and duration of post-traumatic amnesia (PTA) have been shown to be significant predictors of outcome following moderate and severe TBI, research examining their predictive utility in the mTBI population has yielded mixed findings (Carroll, Cassidy, Peloso, et al, 2004). This may be due to the heterogeneous nature of mTBI samples, poor sensitivity of the GCS in this population [i.e., 90% have a GCS of 15/15; Melo et al (2010)], or unreliable assessment of PTA (Shores et al, 2008). However, advanced neuroimaging techniques such as diffusion tensor imaging (DTI), have demonstrated an association between pathophysiological changes following mTBI and persistent PCS (Bigler, 2008;Wilde et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Joseph et al, 15 a mild GCS score (GCS 13-15) in patients with an intracranial injury does not preclude progression on repeat head CT and the need for neurosurgical intervention. Melo et al 16 also indicated that of patients with mild brain injury, neurosurgery was performed in 6.7% and 9.2% had neurological disabilities. In fact, mild brain injury based on GCS score may be associated with significant abnormalities in CT scan, require neurosurgical procedure and Intensive Care Unit admission.…”
Section: Discussionmentioning
confidence: 98%